Signal Processing Of The One-Factor Mean-Reverting Model In Energy System - Pramesti, Getut; Saptono, Ristu (IndoMS, 2025)
One of the models that can be considered in the energy system is the one-factor mean-reverting process. We propose the one-factor mean-reverting model with sinusoidal signal processing involved. The frequency component of the model can be estimated with a high-frequency scheme. The estimation of the frequency component is believed to produce a precise estimate. This is because the high-frequency scheme has the potential to handle possible non-linear coefficient cases in a unified way, that is, nh→ ∞, and nh^2→ 0. This paper shows that the frequency component estimator in the one-factor mean-reverting model is strongly consistent with the rate convergence, namely (nh)^3. It is also can be shown that the estimator has a normal approximation with a mean of 0 and variance 16(1+θ^2). We applied the proposed model to the energy systems data.